Administrative Law Enforcement Concerning Disrespectful Dismissal of Civil Servants in the Perspective of the State Administrative Court - Ahmad Haidar Muiny; Anna Erliyana (Fakultas Hukum Dehasen, 2024)
The administrative law enforcement regarding the dishonorable discharge of Civil Servants (PNS) or State Civil Apparatus (ASN) is a process that involves a series of legal procedures and mechanisms that must be followed by government agencies. From the perspective of the Administrative Court (PTUN), the decision to discharge a Civil Servant or State Civil Apparatus can be reviewed to ensure that the procedures used comply with applicable regulations and that the decision was made fairly and without discrimination. The Administrative Court has the authority to annul the discharge decision if violations of administrative law or principles of justice are found. This study aims to analyze how the Administrative Court evaluates and adjudicates cases of dishonorable discharge of Civil Servants or State Civil Apparatus, as well as to identify the obstacles encountered in the process of enforcing administrative law.